Potential mechanism of action of Ixeris sonchifolia extract injection against cardiovascular diseases revealed by combination of HPLC-Q-TOF-MS, virtual screening and systems pharmacology approach. Issue 63 (20th October 2020) - Xie, Rongfang; Liu, Zhenzhen; Lin, Zuan; Shi, Peiying; Chen, Bing; Li, Shaoguang; Li, Guangwen; Huang, Liying; Lin, Xinhua; Yao, Hong
Abstract : Ixeris sonchifolia extract injection, a Chinese medicine preparation named as Kudiezi injection (KDZI) in China, has been widely used for the treatment of cardiovascular diseases (CVDs) in recent years. Abstract : Ixeris sonchifolia extract injection, a Chinese medicine preparation named as Kudiezi injection (KDZI) in China, has been widely used for the treatment of cardiovascular diseases (CVDs) in recent years. Owing to the component complexity of the preparation, the study on the effect mechanism of the herbal medicine against CVDs is a big challenge. In this research, HPLC-Q-TOF-MS was used to analyze the constituents of the preparation, disclosing that the KDZI mainly consists of 10 ingredients, namely 3-caffeoylquinic acid (KDZI-1), 4-caffeoylquinic acid (KDZI-2), 5-caffeoylquinic acid (KDZI-3), apigenin-7- O -β-d -glucuronide (KDZI-4), caffeic acid (KDZI-5), chicoric acid (KDZI-6), caftaric acid (KDZI-7), luteolin-7- O -β-d -gentiobioside (KDZI-8), luteolin-7- O -β-d -glucopyranoside (KDZI-9) and luteolin-7- O -β-d -glucuronide (KDZI-10). Afterwards, target fishing and an integrated systems pharmacology approach combined with molecular docking (Sybyl 1.3 and AutoDock Vina) were adopted to predict the potential targets and pathways for the main ingredients in KDZI. As results, 39 protein targets and 9 KEGG pathways, possessing high relevance to the therapeutic effects of the ingredients of KDZI against CVDs, were screened out reasonably. The integrated pharmacology analysis suggested that KDZI could exert its therapeutic effects against CVDs possibly via multi-targets including EGFR, MAPK10, and SRC and multi-pathways referring to MAPK, focal adhesion, complement and coagulation cascades, etc . This research provides insights into understanding the comprehensive therapeutic effect and mechanism of the KDZI on CVDs.